PENGARUH HARGA DAN SALURAN DISTRIBUSI TERHADAP KEPUASAN PELANGGAN ROUND SEPARATORS MEREK SWECO PT BANGUN TEKNO KARISMA LESTARI - Wijaya, Ronaldo; Suryatin, Novia; Wilis, Wilis; Anggoro, Muhammad Agung (Aksara Public, 2019)
PT. Bangun Tekno Karisma Lestari is a trading company that distributes Round separators for Sweco and spare parts. The purpose of this study was to examine the effect of Price and Distribution Channels on Customer Satisfaction Round Separator Sweco PT. Build Tekno Karisma Lestari. The method used in this study is a quantitative approach, this type of research is quantitative descriptive, and the nature of this research is descriptive explanatory. The method of data collection is done by interviews, questionnaires, and documentation. The data analysis method used is multiple regression. The population of 133 sample customers is 100 customers. The results showed that simultaneously and partially Price and Distribution Channels had a positive and significant effect on Customer Satisfaction Round Separator Sweco PT. Build Tekno Karisma Lestari.